Progress and challenges in Nipah vaccine development and licensure for epidemic preparedness and response - Sol Kim; Hyolim Kang; Laura Skrip; Sushant Sahastrabuddhe; Ausraful Islam; Sung-Mok Jung; Juan F. Vesga; Akira Endo; W. John Edmunds; Kaja Abbas (Expert Review of Vaccines)
Introduction Nipah virus is a high-consequence pathogen that causes sporadic outbreaks with high mortality, and there are currently no vaccines or therapeutics available for Nipah. Vaccine development against Nipah faces challenges due to its current epidemiology with limited outbreak sizes, which impedes the feasibility of conducting vaccine efficacy trials focused on disease endpoints.Areas covered We review the progress of Nipah vaccine candidates in human clinical trials and highlight the challenges in evaluating the vaccine efficacy due to the sporadic nature of Nipah outbreaks, given the epidemic potential of Nipah virus and its implications for pandemic preparedness. We examine the alternative regulatory pathways, including the US FDA’s Animal Rule and EMA’s conditional marketing authorization, which permit vaccine approval based on surrogate markers rather than efficacy data from the large-scale Phase-3 efficacy trials. The need for standardized immune surrogate markers is emphasized, alongside calls for international collaboration to develop such endpoints and manage stockpile strategies.Expert opinion We recommend alignment among vaccine developers, regulators, and global health stakeholders to incentivize Nipah vaccine development and approval through alternative regulatory pathways, as well as ensuring epidemic preparedness via strategic vaccine stockpiling and response through targeted deployment strategies.